Agronomic performance and industrial quality of bread wheat (Triticum aestivum L.) genotypes cultivated in the northeast of Mexico - Ramírez-Cortez, Nydia; Treviño-Ramírez, José; Pedroza-Flores, Jesús; Urías-Orona, Vania; Salas-Cruz, Lidia; Niño-Medina, Guillermo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Wheat is one of the main crops worldwide, it is distributed in different climatic, ecological and geographical regions around the world, being a basic food for human nutrition. The search for genotypes that have to different environments is a common practice in agriculture. The objective of this study was to evaluate the agronomic performance and industrial quality of four genotypes of bread wheat (BW), namely, BW1 (Control) (San Isidro NL M-2012), BW2 (Floreña NL M-2012), BW3 (Norteña F2007), and BW4 (Conatrigo F2015). Wheat genotypes were evaluated using a complete randomized block design with four replicates. Based on results, BW4 (Conatrigo F2015) had better agronomic performance with higher results in spike length (11.10 ± 0.38), number of spikelets per spike (18.78 ± 0.91), number grains per spike (55.65 ± 7.13), grain yield per hectare (6.42 ± 1.29), forage per hectare (12.25 ± 1.30), and L* in the flour (88.74 ± 0.15). BW4 (Conatrigo F2015) also had the lower weight loss (10.15 ± 1.30) and the higher L* in crust (68.55 ± 0.09). In conclusion, genotypes evaluated in the present work had similar or better results in most of the agronomic performance and industrial quality compared with BW1 (Control) (San Isidro NL M-2012), being BW4 (Conatrigo F2015) the outstanding genotype.